Relations between Activation and Inhibition of Fibrinolysis in the Walls of Human Arteries and Veins - Hegt, Vincent Noordhoek (Thrombosis and Haemostasis, 1977)
From systematic studies of both the activation and the inhibition of fibrinolysis in human blood vessels, data which provided insight into the fibrinolysis antagonism along and across the human vessel wall were obtained.The capacity for fibrinolysis initiated by plasminogen activator in sections of human arteries and veins as demonstrated by the fibrin sfide technique differed greatly along and across the vessel walls. Inhibition of plasmin fibrinolysis in these blood vessels as detected by the fibrin slide sandwich technique was present at sites of low fibrinolytic activity, while inhibition was absent in areas showing strong fibrinolysis. Fibrinolysis was related to endothelial cells, while inhibition of fibrinolysis was brought about by smooth muscle cells. The results indicate that differences in endothelial fibrinolysis may be the result of differences in inhibition of fibrinolysis caused by variations in the number of smooth muscle cells present locally. A systemic decrease in endothelial fibrinolysis observed in endotoxin shock, hyaline membrane disease and a Waterhouse-Friderichsen syndrome appeared to be associated with a systemic increase in inhibition of fibrinolysis not related to smooth muscle cells.